2004
DOI: 10.1104/pp.104.040899
|View full text |Cite
|
Sign up to set email alerts
|

The orf13 T-DNA Gene of Agrobacterium rhizogenes Confers Meristematic Competence to Differentiated Cells

Abstract: Plant infections by the soil bacterium Agrobacterium rhizogenes result in neoplastic disease with the formation of hairy roots at the site of infection. Expression of a set of oncogenes residing on the stably integrated T-DNA is responsible for the disease symptoms. Besides the rol (root locus) genes, which are essential for the formation of hairy roots, the open reading frame orf13 mediates cytokinin-like effects, suggesting an interaction with hormone signaling pathways. Here we show that ORF13 induced ectop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 57 publications
0
24
0
1
Order By: Relevance
“…The predicted amino acid sequence of 6b is somewhat similar to those of a number of proteins encoded by other genes, such as rolB and ORF13 in Ri plasmids, which also cause aberrant growth and the abnormal morphology of both roots and shoots (Spena et al, 1987;Levesque et al, 1988;Stieger et al, 2004). The product of ORF13 has a retinoblastoma binding motif (LXCXE) and interacts with maize (Zea mays) Rb in vitro (Stieger et al, 2004).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The predicted amino acid sequence of 6b is somewhat similar to those of a number of proteins encoded by other genes, such as rolB and ORF13 in Ri plasmids, which also cause aberrant growth and the abnormal morphology of both roots and shoots (Spena et al, 1987;Levesque et al, 1988;Stieger et al, 2004). The product of ORF13 has a retinoblastoma binding motif (LXCXE) and interacts with maize (Zea mays) Rb in vitro (Stieger et al, 2004).…”
Section: Introductionmentioning
confidence: 83%
“…The product of ORF13 has a retinoblastoma binding motif (LXCXE) and interacts with maize (Zea mays) Rb in vitro (Stieger et al, 2004). RolB, which includes a Tyr phosphatase motif (CX5R), has phosphatase activity (Filippini et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The ORF13 and ORF14 genes are found to be highly conserved among A. rhizogenes strains (Stieger et al 2004). It has been demonstrated that alone A4-rolABC genes carried by an Agrobacterium strain are showed to be incapable of inducing rooting on carrot disc and aux genes located on the T R -DNA or ORF13 and ORF14 located on T L -DNA are also required for rooting (Cardarelli et al 1987b;Capone et al 1989).…”
Section: Orf13andorf14mentioning
confidence: 99%
“…Stieger et al (2004) claimed that a proliferative effect of ORF13 expression in the shoot apical meristem (SAM) caused increased number of mitoses and showed no influence on meristem structure. In consequence, the reductions of cell and meristem sizes and the retardation in the formation of leaf primordia were observed.…”
Section: Orf13andorf14mentioning
confidence: 99%
“…The predicted amino acid sequence of 6b is distantly related to the RolB family proteins, whose expression also results in aberrant growth and abnormal morphology of both roots and shoots (Spena et al 1987;Levesque et al 1988;Stieger et al 2004). Protein 6b localizes to the nucleus and was reported to bind to several nuclear proteins-such as NtSIP1 (Nicotiana tabacum Six-b-interacting protein 1) (Kitakura et al 2002), NtSIP2 (Kitakura et al 2008), and histone H3 (Terakura et al 2007)-and affects the expression of various plant genes in transgenic Arabidopsis.…”
mentioning
confidence: 99%